Revisit to the Impacts of Rattlers on Thermal Conductivity of Clathrates - Chen, Cuncun; Zhang, Zhongwei; Chen, Jie (Frontiers in Energy Research, 2018)
Energy conversion from waste heat to electric power is a promising approach for energy harvest, and the clathrates crystals have received lots of attentions in this field from the concept of ‘phonon-glass and electron-crystal’. However, the thermal transport mechanisms and roles of rattlers have yet been clearly revealed in clathrates. By using iterative solution of Peierls-Boltzmann transport equation and first principle calculations, we have systematically revisited the thermal transport properties of a simple binary representative of clathrates, Ba8Si46. Our results confirm that the suppressed phonon lifetime is responsible for the huge reduction of lattice thermal conductivity (κ_l) in clathrates, in addition to the decrease of phonon group velocity. Furthermore, we clarify that phonon scatterings in a wide frequency range and the resonant characteristic scatterings coexist in clathrates, due to the emergence of hybridized modes introduced by the rattlers. We also elucidate that the hybridized modes dramatically suppress the acoustic phonon contribution to κ_l, leading to the non-negligible relative contribution from optical phonon to thermal transport in clathrates. Moreover, the impacts of the hybridized modes on different scattering channels in the phase space are also discussed. Our study provides fundamental physical insights into the impacts of rattlers on thermal conductivity of clathrates, which is valuable towards the design of efficient thermoelectric materials based on the concept of ‘phonon-glass and electron-crystal’.